A Case of Hepatic Angiomyolipoma Which Was Misdiagnosed as Hepatocellular Carcinoma in a Hepatitis B Carrier - Jin Yeon Hwang; Sung Wook Lee; Yang Hyun Baek; Jong Han Kim; Ha Yeon Kim; Suck Hyang Bae; Jin Han Cho; Hee Jin Kwon; Jin Sook Jeong; Young Hoon Roh; Sang Young Han (Case Reports in Hepatology)
We report a rare case of resected hepatic AML, which was misdiagnosed as hepatocellular carcinoma in a chronic hepatitis B carrier. A 45-year-old woman who was a carrier of hepatitis B virus infection presented with a hepatic tumor. Her serum alpha-fetoprotein level was normal. Ultrasonography revealed a round and well-circumscribed echogenic hepatic tumor measuring 2.5 cm in the segment VI. On contrast-enhanced computed tomography, a hypervascular tumor was observed in the arterial phase and washing-out of the contrast medium in the portal phase and delayed phase. On MR T1-weighted in-phase images, the mass showed low signal intensity, and on out-of-phase images, the mass showed signal drop and dark signal intensity. On MR T2-weighted images, the mass showed high signal intensity. The mass demonstrated high signal intensity on arterial phase after contrast injection, suggestive of hepatocellular carcinoma. The patient underwent hepatic wedge resection and histopathological diagnosis was a hepatic angiomyolipoma.